Legal Accountability of the Village Head/Lurah in Ensuring the Truth of Juridical Data in the Complete Systematic Land Registration Program - Uum Humairoh; Wira Franciska; Anriz Nazaruddin Halim; Yuhelson (Global Scientific Publishing, 2023)
Activity registration land systematic done in a manner simultaneously covers all object unregistered registered within the Village / Kelurahan area . In the PTSL Program, the government role active based on a plan Work period long and annual as well as carried out in areas determined by the Minister of ATR/BPN. However in his submission Still Lots society that doesn't own proof on ownership land or proof the No Again available . this _ become constraint for society wants _ submit application registration right on land used owned by custom . Thus , Certificate from Head Village / Lurah become alternative juridical data for ownership ground . But in fact letter information from Head Many villages / lurah ( juridical data ) . raises dispute Because often there is error / manipulation of the owner's data right so that harm party owner right real and engendered dispute later day . Which became tree problem is How not quite enough answer Head Village / Lurah to truth of juridical data If there is errors / data errors that cause loss for party owner real land ? _ And how certainty law for juridical data the ?. In writing This researcher use theory not quite enough answer law of Hans Kelsen and theory Legal certainty from Gustav Radbruch as eye knife analysis
Keywords: Accountability; Juridical Data; PTSL